Effect of salinity stress on germination and early seedling growth of different Safflower (Carthamus tinctorius L.) genotypes - karimi, Naser; Soheilikhah, Zhaleh; Ghasmpour, Hamid Reza; Zebarjadi, Alireza (Journal of Ecobiotechnology, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Elevated soil saline levels resulting from natural geological, hydrological and pedological process, and from using salty water for irrigation may inhibit seed germination and seedling establishment of safflower, the prospective oil-seed crops. A germination study on safflower seeds and a short-term toxicity experiment with different concentrations of NaCl (control, 50, 100 and 200 mM) on safflower seedlings were conducted. Percent germination over control decreased significantly with increasing concentrations of NaCl. There were genotypic differences among the test genotypes in response to salt stress exposure. The performance of the G5 (Gilla) was the best among the genotypes. Germination of G5 was not inhibited at all up to 100 mM NaCl treatment. Root tolerance index (RTI) and relative shoot height (RSH) for safflower seedlings decreased with increasing concentrations of NaCl. In general, G5 (Gilla) has more tolerance to NaCl than the other studied genotypes.